HIV-1 release requires Nef-induced caspase activation - Jason Segura; Joanna Ireland; Zhongcheng Zou; Gwynne Roth; Julianna Buchwald; Thomas J. Shen; Elizabeth Fischer; Susan Moir; Tae-Wook Chun; Peter D. Sun (PLoS ONE, 2023)
HIV infection remains incurable to date and there are no compounds targeted at the viral release. We show here HIV viral release is not spontaneous, rather requires caspases activation and shedding of its adhesion receptor, CD62L. Blocking the caspases activation caused virion tethering by CD62L and the release of deficient viruses. Not only productive experimental HIV infections require caspases activation for viral release, HIV release from both viremic and aviremic patient-derived CD4 T cells also require caspase activation, suggesting HIV release from cellular viral reservoirs depends on apoptotic shedding of the adhesion receptor. Further transcriptomic analysis of HIV infected CD4 T cells showed a direct contribution of HIV accessory gene Nef to apoptotic caspases activation. Current HIV cure focuses on the elimination of latent cellular HIV reservoirs that are resistant to infection-induced cell death. This has led to therapeutic strategies to stimulate T cell apoptosis in a “kick and kill” approach. Our current work has shifted the paradigm on HIV-induced apoptosis and suggests such approach would risk to induce HIV release and thus be counter-productive. Instead, our study supports targeting of viral reservoir release by inhibiting of caspases activation.